Understanding the implications of choice of deprivation index for measuring consistent poverty in Ireland - Christopher T. Whelan (The Economic and Social Research Institute (ESRI), 2007)
In this paper we make use of the Irish component of the European Union Community Statistics on Income and Living Conditions (EU-SILC) survey for 2004 in order to develop a measure of consistent poverty that overcomes some of the difficulties associated with the original indicators employed as targets in the Irish National Anti-Poverty Strategy. Our analysis leads us to propose a set of economic strain items that covers a broader range than the original basic deprivation set and provides a more reliable and valid measure Consistent poverty measures incorporating the revised measure of economic strain and adopting a threshold of two or more items provide similar estimates of levels of poverty to the original measure. However, the new measure is more strongly associated with, respectively, current income, surrogates for permanent income and subjective economic pressures. Furthermore, by constructing a consistent poverty typology we are able to demonstrate that when we contrast those defined as poor when employing the new eleven-item index but not the eight-item one with those for whom the opposite is true the former display a multidimensional deprivation profile that is substantially less favourable. The accumulated evidence supports the view that the revised consistent poverty measures, which combine a threshold of two or more items on the eleven-item EU-SILC11 index with income poverty, identifies those exposed to generalised deprivation arising from lack of resources in a manner consistent with their use as targets in the National Anti-Poverty Strategy.
Keywords: 330; Armut; Soziale Lage; Messung; Irland